Comment on “Continuous g-Frame in Hilbert -Modules” - Zhong-Qi Xiang (Abstract and Applied Analysis)
The continuous g-frames in Hilbert -modules were introduced and investigated by Kouchi and Nazari (2011). They also studied the continuous g-Riesz basis and a characterization for it was presented by using the synthesis operator. However, we found that there is an error in the proof. The purpose of this paper is to improve their result by introducing the so-called modular continuous g-Riesz basis.